Analysis of STEAM-Based Learning through “Fruit Skewers” Fun Cooking Activities for Early Childhood - Amalia Husna; Putri Permata Sari; Yennizar. N (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the implementation of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach in the “Fruit Skewer” fun cooking activity and its impact on early childhood development at TK Aisyah Islamic Preschool. A descriptive qualitative method with a case study approach was employed. Data were collected through participatory observation, semi-structured interviews, and documentation. The results show that all five STEAM components can be effectively integrated into a single contextual and enjoyable learning activity. Science was reflected in the exploration of fruit types, tastes, textures, and benefits; technology through the use of simple cooking tools; engineering through the stages of assembling the fruit skewers; art through aesthetically arranging the fruit pieces; and mathematics through activities such as counting, classifying, and patterning. This activity had a positive impact on various aspects of children’s development, including cognitive, language, fine motor, social-emotional, creativity, and character. STEAM-based learning through fun cooking not only increased children's interest and engagement but also fostered 21st-century skills holistically. This study recommends similar activities as innovative learning strategies that are relevant for implementation in early childhood education settings.